''United Airways Disease'' and Phenotypic Peculiarities of Respiratory Allergy in Immigrants - Carlo Lombardi; Giovanni Passalaqua; Giorgio Walter Canonica (World Allergy Organization Journal, 2009)
Allergy is the result of a complex interaction between genetic background and environmental factors, including exposure to allergens and lifestyle. Migration is a process that involves many radical changes in the environment, including diet, pollutants, allergens, different housing conditions, and patterns of infections. Thus, studies in immigrants may provide important information about the role of environmental factors in the development of allergic respiratory diseases. Several studies addressed this aspect and consistently found that migrants develop allergies at different rates from the local population, and very often the symptoms appear with a delay of 3 to 5 years after migration. More recent data showed that the severity of allergic diseases is greater in migrants, and that usually the onset is with associated asthma and rhinitis. The immigration model strongly suggests that environmental factors overcome the genetic background, and that the clinical phenotype of respiratory allergy in migrants has some peculiarities. Keywords: asthma, rhinitis, allergy, immigration, migrants